Evaluating the effectiveness of development of methods of protection of information systems in the conflict - Гузий, Н. Н. (Problems of Informatization and Control, 2008)
The evaluation of the effectiveness of the development of methods of protection in terms of the uncertainty of the information counter , optimal equilibrium operating expenses side , the presence of errors in the source data challenges and competition in the market of methods of defense and attack in conflicting information systems